2021
DOI: 10.1002/macp.202100062
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Binary Solvent Additive‐Processed Organic Solar Cells by the Blade‐Coating Method

Abstract: Blade-coating, a prototype tool for slot-die coating is a promising technique showing high compatibility with large-area roll-to-roll coating. Here, a high-performance PM6:Y6-based device is fabricated with chlorobenzene (CB) through a novel binary solvent additive (1-chloronaphthalene (CN):diphenyl ether (DPE)). It can be found that the binary solvent additive can improve the crystallinity of the acceptor and forms a better phase separation domain, which would promote the effective separation of charge and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Routes to overcome such an issue include introducing alternative additives, [55] binary solvent additives, [56] nonvolatile solid additives, and third components as in ternary OSCs. [15,57] For example, we have previously substituted the halogen element Cl in the CN molecule with F or Br to mitigate phase separation in PM6:Y6 OSCs and achieved 17.5% PCE.…”
Section: Discussionmentioning
confidence: 99%
“…Routes to overcome such an issue include introducing alternative additives, [55] binary solvent additives, [56] nonvolatile solid additives, and third components as in ternary OSCs. [15,57] For example, we have previously substituted the halogen element Cl in the CN molecule with F or Br to mitigate phase separation in PM6:Y6 OSCs and achieved 17.5% PCE.…”
Section: Discussionmentioning
confidence: 99%
“…162 Fo et al reported binary solvents composed of 1-chloronaphthalene (CN) and diphenyl ether (DPE) as additives to improve the crystallinity and phase segregation domain of the acceptor material, which in turn inhibits charge recombination and enhances power conversion efficiency. 163 In addition to the organic semiconductors, the binary solvent system has also been studied on other types of semiconductors such as small molecular MoS 2 , and C 60 . For example, Majd et al reported a binary solvent method composed of N,N -dimethylformamide (DMF) and IPA to obtain two-dimensional MoS 2 nanosheets with an enlarged surface area for application in detecting miRNA-155 in breast cancer.…”
Section: Binary Solvent Techniquementioning
confidence: 99%
“…4,5 Several methodologies, such as thermal annealing (TA), 6 vapor annealing, 7 and processing additives, 8,9 have been developed to achieve a ne morphology with optimal nanoscale phase separation. Among these techniques, the introduction of additives, such as 1,8-diiodooctane (DIO), 10,11 1-chloronaphthalene (CN), 12,13 and diphenyl ether (DPE), 14,15 into the host solvent has been widely employed to optimize the nanomorphology of the active layer because of its facile and efficient processability. The presence of solvent additives with a high boiling point and selective solubility reduces the overaggregation of small-molecule acceptors in photoactive lms, resulting in a favorable BHJ morphology.…”
Section: Introductionmentioning
confidence: 99%